Design of OpenFOAM mesh generation client software based on C/S architecture - Zhang Zhida; Huai Xiaoyong; Gao Ruochen (Dianzi Jishu Yingyong, 2022)
To meet the requirements of human-computer interaction of OpenFOAM deployed in the cloud GUI, this paper designs and implements an OpenFOAM mesh generation client software. The client software uses plug-in architecture design, which consists of public module, custom module and mesh generation plugins. The GUI of mesh generation is implemented by plugins, which improves the scalability of the software.The client and the OpenFOAM service deployed in the cloud form a C/S architecture. The client remotely invokes the OpenFOAM mesh generation computing service on the cloud through the mesh generation protocol, and builds a user interaction interface according to the service interface specification, realizing cloud collaboration mesh calculation function. An example of mesh generation is given to illustrate that the client software can implement a complete mesh generation process by remotely invoking the service.